The challenge of reducing diesel consumption and greenhouse gas emissions: A perspective on the use of hydrogen in mining trucks - Figueiredo, Robson Lage; Ortiz, Carlos Enrique Arroyo; Silva, José Margarida (Wydział Geoinżynierii, Górnictwa i Geologii Politechniki Wrocławskiej, 2024)
In mining, the traditional system of operation relies on equipment that consumes large amounts of energy. In mine operations, trucks are widely used due to their flexibility, loading capacity, and adaptability to various terrain conditions. However, they have high diesel oil consumption and high emission rates of smoke, particulate matter, and mainly carbon gas from diesel engines. This article offers a comprehensive view on the effect of hydrogen added to the diesel engine in the search for renewable energy alternatives that are in tune with the reduction of the environmental impact arising from the use of petroleum-derived fuels. The article presents an overview about the challenges in reducing the diesel fuel consumption of trucks em-ployed in mining. It approaches the effect of controlled hydrogen addition on diesel engine performance, consumption reduction, and greenhouse gas emissions. Followed by a discussion of the main technologies used to manufacture hydrogen and their production costs. The results of the studies show that hydrogen is a promising alternative for reducing operational, energy, and emissions costs, mainly carbon dioxide (CO2) and carbon monoxide (CO), but it faces barriers in production, storage, and supply costs. We highlight the “green hydrogen”, carbon-free, which contributes to the decarbonization process in mines, as open pit or underground ones.
Mining Science, Vol. 31, 2024, s. 7-20
Keywords: górnictwo; geologia; geoinżynieria; diesel oil; hydrogen; consumption; emissions; decarbonization